Relationship of zonulin levels with thyroid function and metabolic parameters in Hashimoto's thyroiditis (Annals of Medical Research, 2022)
Aim: Intestinal permeability is one of the factors responsible for the pathogenesis of many immune-related diseases, one of which is Hashimoto's-thyroid (HT). We used zonulin as a biomarker of intestinal permeability in this cross-sectional study. We aimed to determine serum zonulin levels in individuals diagnosed with HT and to investigate the relationship between zonulin and autoimmunity biomarkers, thyroid function and metabolic parameters.Materials and Methods: The study was conducted with 43 women newly diagnosed with HT and a control group of 30 matched with them. The evaluated parameters were thyroperoxidase-antibody (TPO-AB), thyroglobulin-antibody (Tg-AB), thyroid hormone profile, metabolic parameters and zonulin levels.Results: Higher levels of TSH, TPO-AB, Tg-AB, TG and TC were measured in the HT group compared to controls (P